Correlations and Event-by-Event Fluctuations in High Multiplicity Events Produced in 208Pb-208Pb Collisions - Shakeel Ahmad; Shaista Khan; Ashwini Kumar; Arpit Singh; A. Ahmad; B. K. Singh (Advances in High Energy Physics)
Analysis of high multiplicity events produced in 158A GeV/c 208Pb-208Pb collisions is carried out to study the event-by-event fluctuations. The findings reveal that the method of scaled factorial moments can be used to identify the events having densely populated narrow phase space bins. A few events sorted out by adopting this approach are individually analyzed. It is observed that these events do exhibit large fluctuations in their pseudorapidity, η, and azimuthal angle, ϕ, distributions arising due to some dynamical reasons. Two-particle Δη-Δϕ correlation study applied to these events too indicates that some complex two-dimensional structure of significantly high magnitude is present in these events which might have some dynamical origin. The findings reveal that the method of scaled factorial moments may be used as an effective triggering for events with large dynamical fluctuations.